Criminal Acts of Gratification of State Civil Apparatus According to Positive Law and Islamic Law in Jambi Province - Suhendry, Suhendry; Umar, Hasbi; Gani, Ruslan Abdu (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Basically, gratification is not a negative thing and something wrong, but the basis for the formation of regulations on gratification is a form of awareness that gratification can have a negative impact and can be misused. This study uses a descriptive qualitative sociological legal research method with a purposive sampling technique. Furthermore, data collection techniques use Observation, interviews, Questionnaires, documentation studies and data analysis. The results of this study found that first, the act of gratification legally violates Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption. While in Islamic Law, gratification is forbidden. Second, the procedure for resolving cases of criminal acts of gratification, namely: investigation, prosecution, trial, and execution of punishment. Third, the factors causing gratification: 1). the mindset of society. 2) lack of moral commitment of the State Civil Apparatus. 3) Economy. 4) Weak supervision of leaders. 5) Weak law enforcement. 6) Low punishment. Fourth, the efforts made are 1) Instilling a culture of not giving in society. 2) Increasing the understanding of State Civil Apparatus not to accept gratification. 3) Improving the quality of law enforcement. 4) Severe punishment for perpetrators of gratification. The results of this study are recommended to: first, the Jambi Provincial Government provides support for State Civil Apparatus to reject gratification. Second, the Education Office provides sanctions in the form of dishonorable dismissal to State Civil Apparatus who commit gratification. Third, Law Enforcement Officers thoroughly investigate State Civil Apparatus who commit gratification and give severe punishment. Fourth, the community does not give gratification in any form.